Thermal behaviour of corn starch granules under action of fungal alpha-amylase - Lacerda, L. G.; da Silva Carvalho Filho, M. A.; Demiate, I. M.; Bannach, Gilbert [UNESP]; Ionashiro, Massao [UNESP]; Schnitzler, E. (Springer, 2008)
Corn starch, partially hydrolyzed by fungal alpha-amylase was investigated by using thermal analysis, microscopy and X-ray diffraction. After enzymatic treatment lower degradation onset temperatures were observed. DSC analysis showed almost similar range of gelatinization temperature, however, the enthalpies of gelatinization increased for the partially hydrolyzed starch granules. According to the X-ray diffraction analysis, stronger cereal pattern peaks were recognized after enzymatic digestion. The results suggested that the hydrolysis was more pronounced in the amorphous part of the starch granules.
Keywords: enzyme; hydrolysis; starch; thermal analysis